Educational pathways: Young Peruvians in the COVID-19 pandemic - Arangoitia, VR; Crivello, G; Leon, AA (Young Lives, 2023)
This paper presents findings from the second instalment of a telephone follow-up study conducted over two consecutive years, 2020 and 2021, with the Younger Cohort (19- and 20-year-olds) of the qualitative longitudinal Niños del Milenio (Young Lives) study in Peru. This study aims to highlight the changes and continuities in the educational challenges faced by young people in relation to the COVID-19 crisis.